2002
DOI: 10.1136/jnnp.72.2.262
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 expression is increased in oedematous human brain tumours

Abstract: Aquaporin-4 (AQP4) is a highly conserved water channel protein. In rats, AQP4 is expressed in astrocyte foot processes and is important in brain water homeostasis. AQP4 expression has not been investigated in non-neoplastic human brain or oedematous brain tumours, where water homeostasis is disrupted. Therefore, immunohistochemistry was used to study AQP4 expression in non-neoplastic and neoplastic human brain and blood-brain barrier permeability was assessed using contrast enhanced computed tomograms. AQP4 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
245
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 348 publications
(261 citation statements)
references
References 19 publications
(21 reference statements)
10
245
2
4
Order By: Relevance
“…Further studies are needed to clarify the mechanisms responsible for the upregulation of AQP1 (present study) and AQP4 (Saadoun et al, 2002) expression in brain tumours and the contribution of these water channels to brain tumour oedema. Co-cultures of neurons, astrocytes, endothelial or cancer cells may elucidate the role of cell-cell interactions in the control of water channel expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Further studies are needed to clarify the mechanisms responsible for the upregulation of AQP1 (present study) and AQP4 (Saadoun et al, 2002) expression in brain tumours and the contribution of these water channels to brain tumour oedema. Co-cultures of neurons, astrocytes, endothelial or cancer cells may elucidate the role of cell-cell interactions in the control of water channel expression.…”
Section: Discussionmentioning
confidence: 92%
“…AQP1 is expressed in choroid plexus epithelium and may be important in the formation of cerebrospinal fluid (Verkman and Mitra, 2001). In man, there is massive upregulation of AQP4 expression in tumour cells in high-grade astrocytomas and reactive astrocytes around metastatic carcinomas (Saadoun et al, 2002). However, little is known about AQP1 expression in normal human brain and human brain tumours.…”
mentioning
confidence: 99%
“…For some tumors, positive correlations have been established between histological tumor grade and the amount of AQP expression, as for AQP4 expression in diffuse astrocytomas [5,6]. The four studies reporting reduced AQP expression in tumors should be interpreted with caution because only single AQPs were studied without exploring the possibility that other AQPs may be upregulated.…”
Section: Aqp Expression In Tumorsmentioning
confidence: 99%
“…Tumor AQP expression may thus cause tumor expansion by exacerbating tumor-associated edema, a particularly troublesome complication in the case of brain tumors. In astrocytomas, for example, tumor AQP4 expression correlates with the amount of edema but not with patient survival [6,9]. Because of the noncompliant skull, brain tumor edema contributes to increased intracranial pressure, which reduces cerebral blood flow and produces brain herniation.…”
Section: Aqp Expression In Tumorsmentioning
confidence: 99%
“…Moreover, several lines of evidence have linked AQP4 to neuroinflammation. AQP4 is involved or upregulated in several neuroinflammatory diseases, such as NMO (339), MS (338), acute bacterial meningitis (340), pathological inflammation induced by LPC-(335) and LPS injections (336) as well as conditions that induce secondary inflammation, including stroke (292,453), tumor (329,450), in addition to chronic neurodegenerative diseases (342, 343, 345, 346, 348-350, 364, 365). Moreover, it has been shown that pro-inflammatory cytokines can serve as signal molecules for upregulation of astrocytic AQP4 in vitro (337).…”
Section: Selective Vulnerability Mediated By the Glial Microenvironmementioning
confidence: 99%